1998
DOI: 10.1016/s0005-2728(98)00097-8
|View full text |Cite
|
Sign up to set email alerts
|

Essential structural factors of annonaceous acetogenins as potent inhibitors of mitochondrial complex I

Abstract: The annonaceous acetogenins are the most potent of the known inhibitors of bovine heart mitochondrial complex I. These inhibitors act, at the terminal electron transfer step of the enzyme, in a similar way to the usual complex I inhibitors, such as piericidin A and rotenone; however, structural similarities are not apparent between the acetogenins and these known complex I inhibitors. A systematic set of isolated natural acetogenins was prepared and examined for their inhibitory actions with bovine heart mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
91
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 31 publications
13
91
0
2
Order By: Relevance
“…The inhibition of compound 2 was about 5-fold less potent than that of compound 1 (Table 1). At first sight, this difference seems to be not so significant, but it should be noted that inhibitory potencies of stereoisomers of common acetogenins are almost identical irrespective of the number of THF rings (9,12,13). Therefore, this result indicates that the effect of stereochemistry surrounding the bis-THF rings is more important for ∆lac-acetogenin than for common acetogenins.…”
Section: Crucial Structural Factors In the Thf Ring Moietymentioning
confidence: 88%
See 1 more Smart Citation
“…The inhibition of compound 2 was about 5-fold less potent than that of compound 1 (Table 1). At first sight, this difference seems to be not so significant, but it should be noted that inhibitory potencies of stereoisomers of common acetogenins are almost identical irrespective of the number of THF rings (9,12,13). Therefore, this result indicates that the effect of stereochemistry surrounding the bis-THF rings is more important for ∆lac-acetogenin than for common acetogenins.…”
Section: Crucial Structural Factors In the Thf Ring Moietymentioning
confidence: 88%
“…In particular, the inhibitory potency of compound 7 possessing two n-butyl groups was equivalent to that of bullatacin, one of the most potent inhibitors of bovine complex I (4,6,9). Replacement of the n-butyl group of compound 7 with a bulky tert-butyl group little affected the activity (compound 7 vs 8).…”
Section: Crucial Structural Factors In the Thf Ring Moietymentioning
confidence: 97%
“…The alkyl chain could result in some sort of specific conformation for optimal spatial position on the enzyme and produce potent activity. [11][12][13] Summarizing the above results and suggestions herein, it was initially thought that the inhibitory potency of ACG probably came from the features of a terminal 2,4-disubstituted-g-lactone combined with other functional ring units (in spite of THF or lactone) by a certain length of alkyl chain. The combination of the three structural factors would offer the basic specific conformation for a spacer on NADH oxidase.…”
Section: Resultsmentioning
confidence: 71%
“…But some reports indicated that the C 4 -OH was not important for the exhibition of potent effects. 11,12) Compound 1 was a new structural product which was characterized by two lactones linked by a alkyl chain. Compared with the weaker potency of compound 1, the greater potency of squamocin C and squamostatin B indicated that the THF possibly played a role in the optimal inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1a and 1b exhibited almost same inhibitory potency, indicating that the stereochemistry around the dihydroxyl moiety does not affect the inhibitory action. 12 It is noteworthy that compared to potent natural ordinary acetogenins such as bullatacin (IC 50 = 0.83 nM) 4 and cis-solamin (IC 50 = 2.6 nM), 13 1a and 1b are much weaker inhibitors of the enzyme. Further comparison with dihydroxy-cohibin-A (IC 50 = 20 nM), 14 which was synthesized by us, the inhibitory activity is quite weak.…”
Section: Inhibitory Action With Bovine Heart Mitochondrial Complex Imentioning
confidence: 99%